Descemet Membrane Endothelial Keratoplasty After Failed Penetrating Keratoplasty. Issue 3 (March 2019) - Pierné, Kévin; Panthier, Christophe; Courtin, Romain; Mazharian, Adrien; Souedan, Vael; Gatinel, Damien; Saad, Alain
Abstract : Purpose: To demonstrate the feasibility of Descemet membrane endothelial keratoplasty (DMEK) performed after previous penetrating keratoplasty (PK) failure and to describe primary outcomes. Methods: Twenty-eight eyes of 28 patients who underwent DMEK after primary PK failure between January 2013 and November 2017 were included in this single-center retrospective study. Best spectacle-corrected visual acuity, endothelial cell density, and the recipient's central corneal thickness were recorded preoperatively and at 1, 3, and 6 months after surgery. Results: The main indications for primary PK were keratoconus (32%), Fuchs dystrophy (18%), and pseudophakic bullous keratopathy (14%). After a 6-month follow-up, best spectacle-corrected visual acuity was significantly improved in 26 patients (93%) with a mean gain of +0.59 ± 0.47 LogMAR ( P < 0.0004). Mean pachymetry reduction was 110 ± 108 μm ( P < 0.00003) at 6 months. Mean endothelial cell density was 2016 ± 288 cells/mm 2 ( P < 0.006), (24% decrease compared with preoperative values). Graft detachment (>1/3) was observed in 14 cases (50%) and rebubbling was needed (100% effective) during the first 2 weeks after surgery. Elevated intraocular pressure was reported in 5 cases. No early graft rejections were reported. Conclusions: In case of previous PK failure, DMEK is an alternative treatment to re-PK. A longer follow-up to ensure the long-term viability of the graft is needed.